Measurement report: Diurnal variability in NO2 and HCHO lower-tropospheric vertical profiles in southeastern Los Angeles - P. K. Peterson; L. F. Hernandez; L. Tanaka; A. Dunnick (Atmospheric Chemistry and Physics)
Ground-level ozone in excess of the United States National Ambient Air Quality Standards remains a prevalent issue across Southern California, particularly in the summer months. To improve our understanding of the vertical distribution of ozone precursors in Southern California, we used ground-based multi-axis differential absorption spectroscopy (MAX-DOAS) measurements in Whittier, California, to simultaneously retrieve both near-surface mole fractions and vertical column densities (VCDs) of both NO2 and HCHO. Ratios of HCHO to NO2, commonly referred to as FNR, derived from satellite-based measurements are used to diagnose ozone production chemistry over regions without consistent surface-based measurements. While VCDs of NO2 are well correlated with TROPOMI observations over the study period (R=0.73), HCHO VCDs and FNRs derived from MAX-DOAS observations are less well correlated (R=0.48 and 0.59, respectively). These observations also showed differing diurnal cycles between near-surface mixing ratios and VCDs due to variability in the vertical profile; this diurnal behavior will be increasingly critical to understand given the ongoing shift from Sun-synchronous to geostationary satellite observations. Using ground-based measurements, we determined FNRs using both surface mole fractions and VCDs, finding that FNRs derived from surface mole fractions are generally lower than those derived from column-based measurements. Evaluating the ozone exceedance probability as a function of FNR for both quantities suggests that the transition from volatile organic compound (VOC)-limited to NOx-limited regimes may begin at lower FNR values than those derived from satellite-based measurements in East Los Angeles. We find that these differences in FNRs derived from ground-based and satellite-based measurements are driven by variability in the vertical distribution of HCHO. These impacts are most pronounced in late afternoon, when ozone exceedances are most prevalent.